Leachate Monitoring and an Assessment of Groundwater Pollution from the Tangier Landfill - Elmaghnougi, Ikram; Tribak, Abdelghani Afailal; Maatouk, Mustapha (Geomatics and Environmental Engineering, 2022)
Leachate from public landfill in the city of Tangier, which is neither collected nor treated, could constitute a probable source of pollution of the groundwater table and of those of the Mlalah and Khandak Bou Hajjar wadis in the east, and the Mghogha and Ghir Boudra wadis to the south. This work aims to analyze the level of contamination at Tangier’s municipal waste disposal. The leachate samples were collected and analyzed during the period from 2016 to 2019 and the physicochemical parameters (humidity, pH, organic matter, etc.) were determined on these samples as well as the contents of five heavy metals (lead, cadmium, iron, chrome and zinc). Analysis of the well water shows the presence of polluting elements in the leachate water and a high concentration of metals (especially iron) that exceeds standards. This makes the effluent extremely toxic and thus presents a permanent threat to the health of the local population and the surrounding environment.